2020
DOI: 10.20956/jars.v4i2.2336
|View full text |Cite
|
Sign up to set email alerts
|

Households Travel Behaviour to Markets in Rural Communities in Ayedaade Local Government Area of Osun State, Nigeria

Abstract: Many rural households in Nigeria are less accessible to markets to transact their business. Traders travel considerable distance and pay high transport fare to convey their goods to markets for sale. This is because many rural communities are located farther away from where the markets are situated. It is on this background that this study examined the accessibility of traders to markets in some rural communities in Ayedaade Local Government Area of Osun State. Both primary and secondary data were utilized for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…This nding is consistent with the previous study reported by other researchers in the same country (Adetunji and Adepoju 2011). The authors attested that besides family income level, education and health awareness were other important factors that determine the preference of protein sources by the people.…”
Section: Discussionsupporting
confidence: 93%
“…This nding is consistent with the previous study reported by other researchers in the same country (Adetunji and Adepoju 2011). The authors attested that besides family income level, education and health awareness were other important factors that determine the preference of protein sources by the people.…”
Section: Discussionsupporting
confidence: 93%